(untitled) (Trinity Journal of Management, IT & Media (TJMITM), 2021)
One of the major ways of communicating with the audiences in the media is through writing. And for that, a person should understand the craft properly. Science is about getting objective knowledge. It’s all about asking questions, making observations, and distinguishing between what we know and what we don’t. To understand how things work, science helps us develop rules — laws that should be viewed with skepticism. Writing is also skill based and requires following rules and regulations. To be eloquent i.e. fluent or persuasive in writing requires a proper understanding of the language of the target audience. The science of media writing helps to identify how to use this language to bring more clarity and make it understandable for the target audiences. The aim of this study is to throw light on the what, why, how, where and for whom of media writing. This is a small initiative to bring into notice and understand how to improve your writing skills by understanding the answers to these questions. This paper will bring into light what you can write, why you should write, how to write it, where you can publish it and who your target audience will be. This will eventually improve your writing game and establish you as a skilled communicator in the field of media writing. The study is unique in the sense that an attempt has been made to find out the answers to these questions in the best possible manner by going through various examples and books available in the field of writing.